Foresight as Technology of Strategic Planning - Aleksei Igorevich Balashov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The scientific novelty of the author’s approach is that foresight is regarded as a technology development and monitoring the implementation of the most important documents of strategic planning of urban development. The theoretical basis of the methodology defined by the concept of creative foresight of the city and smart city, allowing to characterize the urban space from the point of view of building a post-industrial development. Proposals to improve the functioning of the system of strategic planning of St. Petersburg, including - the recommendation to expand the panel of experts through the inclusion of a number of groups of representatives of creative and smart dimensions of the urban environment